Raising Awareness on Bullying through a Design Situation and Rationale - da Silva Junior, Deógenes P.; Pereira, Roberto; Baranauskas, M. Cecilia C. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Bullying is a form of violence that occurs in different situations of our social and physical environment, profoundly affecting people’s lives. Digital media can be a facilitator of this misbehavior, but also a supporter in combating it. The literature in computing has shown efforts mainly through web and desktop technologies, with few technologies of Ubiquitous Computing, no exploration of the human values of the interested parties, and few papers exploring bullying’s social and physical dimensions. In this study, we use the theory of Socioenactive Systems and the methodology of Socially Aware Design to design a ubiquitous scenario of interaction aiming to raise awareness against bullying. The value-oriented design process was conducted by three researchers to primarily identify stakeholders of the problem domain, anticipate problems, and values associated with them. Through collaborative brainstorming and brainwriting, a technological artifact was devised using narrative scenarios and prototypes. In this paper we present the design process and the technology-based scenario resulting from the process, and discuss its rationale based on the values raised in our process.